Pharmacological Modulation of Functional Phenotypes of Microglia in Neurodegenerative Diseases - Song, Gyun Jee; Suk, Kyoungho (Frontiers in Aging Neuroscience, 2017)
Microglia are the resident innate immune cells of the central nervous system that mediate brain homeostasis maintenance. Microglia-mediated neuroinflammation is a hallmark shared by various neurodegenerative diseases, including Alzheimer’s disease, Parkinson’s disease, and multiple sclerosis. Numerous studies have shown microglial activation phenotypes to be heterogeneous; however, these microglial phenotypes can largely be categorized as being either M1 or M2 type. Although the specific classification of M1 and M2 functionally polarized microglia remains a topic for debate, the use of functional modulators of microglial phenotypes as potential therapeutic approaches for the treatment of neurodegenerative diseases has garnered considerable attention. This review discusses M1 and M2 microglial phenotypes and their relevance in neurodegenerative disease models, as described in recent literature. The modulation of microglial polarization toward the M2 phenotype may lead to development of future therapeutic and preventive strategies for neuroinflammatory and neurodegenerative diseases. Thus, we focus on recent studies of microglial polarization modulators, with a particular emphasis on the small-molecule compounds and their intracellular target proteins.